STUDENTS’ SOCIO-ECONOMIC SITUATION AND CHOOSING A DEGREE COURSE - Agnieszka Smarzewska; Ewelina Melaniuk; Adam Szepeluk (Rozprawy Społeczne)
Introduction The moment students choose their degree course allows for analysing their economic situation. The aim of the article was to research the impact of socio-economic conditions on students’ selection of the degree course.